Phosphorus Sorption Capacity and Its Relationships With Soil Properties Under Podzolic Soils of Atlantic Canada - Kedir, Amana Jemal; Nyiraneza, Judith; Hawboldt, Kelly Anne; McKenzie, David Bruce; Unc, Adrian (Frontiers in Soil Science, 2022)
Repetitive long-term fertilizer application leads to phosphorus (P) accumulation in agricultural soils. This can pose environmental risks if the soil’s phosphorus storage capacity is not well understood and considered when planning nutrient management. We investigated the P sorption capacity (PSC) in the surface (0-20 cm, n = 23) and subsurface (20-40 cm, n = 23) of long-term managed podzolic soils in Newfoundland (Nfld), Canada, through batch adsorption using two P concentrations of 150 and 500 mg P L-1, and developed pedotransfer functions to estimate PSC using selected soil properties. Also, the correlation between actual PSC, soil properties, and estimated Phosphorus saturation index (PSI) and soil P sorption capacity (SPSC) both from standard soil test were evaluated. The surface and subsurface soils provided similar median PSC (1.34 and 1.32 mg g-1, respectively, p = 0.16) when examined with the 150 mg P L-1 solution. With 500 mg P L-1 solution, the subsurface soils had significantly higher median PSC than the surface soils of the same fields (2.74 and 2.27 mg g-1, respectively, p = 0.02); and had a better linear relationship (R2 >0.40, p <0.05) with SPSC than at the lower P concentration. The surface soils had significantly higher extractable median P in water, citric acid, and Mehlich-3, higher soil organic matter (SOM), moisture content, Mehlich-3-Fe, -Ca, and -K, PSI, electrical conductivity, silt, and clay contents, while Mehlich-3-Al, Mehlich-3-Al:Fe ratio, SPSC, and sand were lower than those in the subsurface soils. All soils had comparable pH (~6.3). Pedotransfer function revealed that the PSC could be predicted using SOM, Mehlich-3-Al, and Mehlich-3-PICP and thus may be employed for developing testable hypotheses relevant to environmentally and economically viable P management strategies for acidic soils in boreal regions.